Linking performance decline to choking: players` perceptions in basketball - Fryer, A. M.; Tenenbaum, G.; Chow, G. M. (Journal of Sports Sciences, 2018)
This study was aimed at examining how basketball players view unexpected performance errors in basketball, and under what conditions they perceive them as choking. Fifty-three basketball players were randomly assigned into 2 groups (game half) to evaluate the linkage between performance decline and choking as a function of game-time, score gap and game half. Within each group, players viewed 8 scenario clips, which featured a different player conducting an error, and subsequently rated the extent of performance decline, the instance of choking and the salience of various performance attributions regarding the error. The analysis revealed that choking was most salient in the 2nd half of the game, but an error was perceived as choking more saliently in the beginning of the 2nd half. This trend was also shown for players` perception of performance decline. Players` ratings of the attributions assigned to errors, however, revealed that during the end of the 2nd half, time pressure and lack of concentration were the causes of errors. Overall, the results provide evidence towards a conceptual framework linking performance decline to the perception of choking, and that errors conducted by players are perceived as choking when there is not a salient reason to suggest its occurrence.